(3LQjeI JYPjH GdeJge dMedg Ydi GdGYJQGa (B: s (3OQGSI ebGQfI (B/ s - (3CMeO eMeO YHOGdQMef MLGRjs; (3TQja S`jO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JfGhd gPG GdHMK LQjeg JYPjH GdeJge dMedg Ydi GdGYJQGa ai GdbGfhf GdeUQi ebGQfkg eY GdbGfhf GdGeQjci hJYQV ddEJaGbjGJ GdOhdjg GdJi JLQe GdJYPjH heG jdMbg HEQGOg GdeJge ef CKGQ hbO Je GdJYQV dJYQja GdJYPjH ai GdbGfhf GdeUQi hGdGeQjci hGdJYQV dGQcGf GdLQjeg hYbhHGJgG hGdLRGA GdLfGFi hGdeOfi hGdJCOjHi hcPG GdLRGA GdGLQGFi GdeJQJH YdjgG ceG Je GdJYQV ddbhGfjf GdGeQjcjg SjFg GdSeYg GdJi hGab YdjgG GdchfLQS GdGeQjci ai SbWg GNdGbjg deMGhdg GdEdJaGa Ydi GdOSJhQ GdGeQjci hGdbGfhf GdajOQGdi GdGeQjci hPdc HZjg GdJgQH ef GdEdJRGeGJ GdOhdjg HecGaMg GdJYPjH hGdeYGedg Gdegjfg hGdehbY YdjgG ef GdhdGjGJ GdeJMOg GdGeQjcjg hcPG Je GdJYQV dcjajg EKHGJ GdLQjeg hfJGFL GdHMK heG GfJgi Gdjg GdHMK ef JhUjGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B333-347s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI GdJYPjH s; (3GdJYPjHs; (3GdeJges; (3GdQcf GdeaJQVs; (3GdbUO GdLfGFjs; (3YbhHI GdJYPjHs; (3GdLRGA GdeOfjs; (3GdeSGgeIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs